Self-authorship to Create and Shape the Identity of Women in STEM - Sheffield, Rachel; Blackley, Susan; Bennett, Dawn; Fairhurst, N.; Murakami, M.; Forman, R.; Pang, Y. (2017)
Problem: The very low and declining percentage of females undertaking advanced science and mathematics subjects in Year 12 has been noted by the Office of the Chief Scientist (2014) and the Australian Mathematical Sciences Institute (Roberts, 2014). In 2011, only 28% of STEM-employed Australians were female, and this figure dropped to 14% for engineering students (Professionals Australia, 2014). Similar figures are evident in the US where Nobel Laureate Carol Grinder notes not only a deficit of women entering STEM-related fields, but also that many women experience many practical, psychological, and social barriers to continuing and advancing in their STEM careers 1. Given the low level of females employed in STEM-related careers and the high proportion of female primary preservice teachers, the focus on supporting and developing female STEM teachers is crucial. This study asserts that the communication and collaboration between female STEM teachers and females employed in STEM-related industries is key to raising the profile of females in this space, creating communities, and sharing expertise. Plan: To support the development of empowered and resilient women in STEM, the project employed a process of self-authorship (Kegan, 1994) to support and capture the emergent STEM identity of preservice teachers and engineering students. Self-authorship is “the ability to collect, interpret, and analyse information and reflect on one’s own beliefs in order to form judgements” (Baxter Magolda, 1998, p. 143). Self-authorship is “about the cognitive process people use to make meaning” (Creamer & Laughlin, 2005, p. 14). Action: Whilst working as members of a STEM Community of Practice comprising pre-service teachers and engineering students at Curtin University, members (students and academics) participated in guided reflective writing. Guiding questions asked about participants’ interest in STEM, influential others, their self-view as Steminists, how their self-view developed over the period of the project, and how they envisaged their future STEM selves. The Community of Practice was formed during an internally funded Makerspace in STEM project in 2016 that engaged higher education students on campus in a designated physical Makerspace in the Engineering Pavilion, virtually (via a closed Facebook site), and at an Independent Catholic girls’ school in Perth. Reflection: This presentation reports on the initial questions of influence and impact of the project, in particular the Community of Practice as an incubator to nurture professional identity. The narratives authored by the students and the research team (female academics) indicate diverse reasons for participating in the community and the reflections on personal and professional growth were insightful and support the physical and virtual modes of the community.